IMPLEMENTASI MOTION GRAFIS VIDEO ANIMASI 2D UNTUK PENGENALAN NIRMANA - Reno, Terrence; Siahaan, Arta Uly; Alfian, Alfian (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2018)
One of the purpose information technology nowadays is to deliver the information in an interesting way. For example, the using of animation tend to be more interesting to present the information. This project created a 2D animation for introducing Nirmana. Some steps were conducted to finish this product starting with creating the storyboard namely finding the idea and arranging the synopsis, continuing with creating the character sketch and storyboard. After completing this step, the next step is making animation by using Adobe After Effect Software. It is started with editing and composing based on the scene by using Adobe Premiere Pro. Project software. For the final step, the researcher intends to test the using this 2D animation by applying motion graphics as the media for teaching Nirmana to the children. This 2D animation is presented with a colorful layout and completed by voice effect for getting the children’s attention.